Answer:
f(4) = 22
Step-by-step explanation:
I think that you type wrongly.
we have f(1) = -5
and f(n) = f(n-1) + 9
Find f(4)
Then
with n= 2 we have f(2) = f(1) + 9 = - 5+ 9= 4
with n= 3 we have f(3) = f(2) + 9 = 4 + 9= 13
and finally with n= 4 we find f(4) = f(3) + 9 = 13+ 9= 22
So f(4) = 22
Hope you understand.
Answer: Step-by-step explanation:
57 - 10x = 45
-10x=-12
x=1.2
- 3y + 10x = -5
-3y+10=-5
-3y=-15
y=5
Answer:
False
Step-by-step explanation:
To solve this problem, plug in the value for Y, 9, into the inequality.
9 + 3 < 12
Now, solve the inequality. Evaluating 9 + 3, the equation becomes:
12 < 12
12 is not less than 12 (12 = 12), therefore the answer is false.
Answer:
Step-by-step explanation:
we have
-----> equation A
-----> -----> equation B
Substitute equation B in equation A
solve for Y